Arthroscopic Treatment Yields Lower Reoperation Rates than Open Treatment for Native Knee but Not Native Shoulder Septic Arthritis - Ajay S. Padaki, M.D; Gabrielle C. Ma, B.S; Nicole M. Truong, B.S; Charles J. Cogan, M.D; Drew A. Lansdown, M.D; Brian T. Feeley, M.D; C. Benjamin Ma, M.D; Alan L. Zhang, M.D (Elsevier, 2022)
Purpose: To compare the incidence, patient demographics, complication rates, readmission rates, and reoperation rates of open and arthroscopic surgery performed for septic arthritis in native knee and shoulder joints. Methods: Records of patients who were diagnosed with native knee or shoulder septic arthritis and underwent open or arthroscopic irrigation and debridement (I&D) between 2015 and 2018 were queried from the PearlDiver Mariner Database. International Classification of Diseases 10th (ICD-10) diagnosis and procedure codes were used to identify patients and track reoperations. Reoperation procedures, including revision open and arthroscopic I&D, were analyzed at 1 month, 1 year, and 2 years. Complications, emergency department (ED) admissions, and hospital readmissions within 30 days were analyzed and compared between the open and arthroscopic cohorts. Results: The query resulted with 1,993 patients who underwent knee I&D (75.3% arthroscopic, 24.7% open, P < .001) and 476 patients who underwent shoulder I&D (64.8% arthroscopic, 35.2% open, P < .001). One-month complication rates (11.6-22.7%) and hospital readmission rates (15.8-19.6%) were similar for arthroscopic and open treatment for knee and shoulder septic arthritis. Reoperation rates for revision I&D of the knee were higher after open compared to arthroscopic treatment at 1 month, 1 and 2 years (20.9% vs. 16.7%, 32.5% vs 27.6% and 34.1% vs. 29.4%, P < .05, respectively). For shoulder septic arthritis 1-month, 1-year, and 2-year reoperation rates were similar for open and arthroscopic treatment (16.0% vs 11.7%, 22.0% vs 19.3%, and 22.7% vs 20.0%, P = .57, respectively). Lastly, 6.7% of patients with native septic knee arthritis underwent subsequent arthroplasty by 2 years. Conclusion: Arthroscopic treatment carries a lower reoperation rate than open surgery for knee septic arthritis, but in the shoulder, the risk for revision I&D is similar after arthroscopic or open surgery.